Why did the monster cross the road? - Stine, R. L.; Brown, Marc Tolon (New York : Orchard Books, an imprint of Scholastic Inc., 2023)
Hunny and Funny are monster best friends. When Hunny is feeling sad, Funny knows exactly how to cheer up his friend--with laughter!
Publishers Weekly, May 2023
Booklist, May 2023
1.5
K-3
Keywords: Monsters -- Juvenile fiction; Best friends -- Juvenile fiction; Humorous stories; Monsters -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Humorous fiction; Monster fiction; Practical jokes -- Juvenile fiction